Vascular Neurology Board Review An Essential Study Guide - Amin, Hardik P.; Schindler, Joseph L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This concise, yet comprehensive review covers the diagnostic and treatment information needed for the vascular neurology board exam. The assembled material is easy-to-read with chapters emphasizing clinically relevant scientific principles that must be mastered by the stroke clinician. Neurology, vascular neurology and neuro-critical care residents and fellows will find this text to be an invaluable preparation guide and a succinct source to complement treatment guidelines and protocols.
Basic science and pathophysiology of cerebrovascular diseases -- Neuro-anatomy -- Clinical features of cerebrovascular disease -- Epidemiology -- Acute evaluation, treatment and management of stroke/vascular neurology patients -- Intracerebral hemorrhage -- Complications of stroke -- Causes of adult and pediatric stroke Stroke genetics -- Primary and secondary stroke prevention -- Stroke rehabilitation -- Pharmacology -- Neuro-radiology -- Neuro-pathology -- Stroke systems of care.
Keywords: Medicine; Cardiology; Neurology; Medicine & Public Health; Neurology; Cardiology